PENGARUH TINGKAT PENDIDIKAN, KOMITMEN ORGANISASI DAN TEKNOLOGI INFORMASI TERHADAP IMPLEMENTASI STANDAR AKUNTANSI PEMERINTAH BERBASIS AKRUAL (Studi Empiris Pada Satuan Kerja Perangkat Daerah Kabupaten Rokan Hulu Tahun 2015) - Nurwanti Fatimah; Yessi Mutia; Mudrika Alamsyah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
This research aimed to know the Influence Of The Level Education, Organizational Commitment And Information Technology on the implementation of government accounting standards accrual based. The main problem that researcher descriptions are as follows: to see how many significant relationship between the dependent variable to the independent variable. The results of this research showed that the level of education have influence on the implementation of government accounting standards accrual based, organizational commitment have influence on the implementation of government accounting standards accrual based, and Information Technology have influence on the implementation of government accounting standards accrual based. So that all the hypotheses presented in this research received.Keywords: government accounting standards, accrual based, implementation, level education, organizational commitment, information technology.